Homogeneous catalysis : mechanisms and industrial applications - Bhaduri, Sumit, 1948-; Mukesh, Doble (Wiley, 2014)
"Providing a balanced treatment of the recent breakthroughs and developments while also detailing earlier discoveries and the fundamentals of homogeneous catalysis, the text provides problems and answers, along with real-life case studies, extensive references to cutting-edge research with application potential and leading patents, and examples from proven industrial processes with clear discussions on environmental and techno-commercial issues"--